CSIG-04. ROLE OF c-Met/β1 INTEGRIN COMPLEX IN THE METASTATIC CASCADE. (9th November 2020) - Sudhir, Sweta; Lau, Darryl; Wadhwa, Harsh; Jain, Saket; Chandra, Ankush; Nguyen, Alan; Spatz, Jordan; Shah, Sumedh; Cheng, Justin; Safaee, Michael; Yagnik, Garima; Jahangiri, Arman; et al.
Abstract: Metastases cause 90% of human cancer deaths. The metastatic cascade involves 5 steps: local invasion, intravasation, extravasation, metastatic site colonization, and proliferation. While individual mediators of these processes have been investigated, interactions between these mediators remain less well defined. We previously identified a structural complex between receptor tyrosine kinase c-Met and β1 integrin in metastases that form under certain biological and therapeutic inducers, including bevacizumab. Using novel cell culture and in vivo assays, we found that c-Met/β1 complex induction promotes breast cancer intravasation and adhesion to the vessel wall but does not increase extravasation. These effects may be driven by the ability of the c-Met/β1 complex to increase mesenchymal and stem cell characteristics in breast cancer cells. Multiplex transcriptomic analysis revealed upregulated Wnt and hedgehog pathways after c-Met/β1 complex induction in breast cancer cells. We subsequently used CRISPR to introduce a β1 integrin point mutation that prevented binding to c-Met and led to reduced intravasation, confirming the importance of c-Met/β1 integrin binding for the metastatic cascade. OS2966, a therapeutic B1 integrin blocking antibody, disrupted c-Met/β1 binding as well, and decreased invasion, mesenchymal gene expression, and mesenchymal morphology of breast cancer cells. Bone-seeking breast cancer cells exhibited higher c-Met/β1 complex levels than parental controls and preferentially adhere to tissue-specific matrix. Patient bone metastases demonstrated higher c-Met/β1 complex levels than brain metastases. Thus, our research suggests the c-Met/β1 complex drives breast cancer cell intravasation and preferential affinity for bone tissue-specific matrix. Pharmacological targeting of the complex may prevent metastases, particularly osseous metastases.